Information systems architecture and technology. proceedings of 39th International Conference on Information Systems Architecture and Technology – ISAT 2018 /: proceedings of 39th International Conference on Information Systems Architecture and Technology – ISAT 2018. Part III : ([2019]) - Unknown
No abstract available